Power blues ; Bucking the system ; The Eraserheads [videorecording] - Lazaro, Cheche (The Probe team, 1994)
The three parts viewed are : the Masinloc coal-fired power plant operation being protested by environmentalists and blocking the governments power development programs; the people in the judiciary charged of graft and corruption in 1993 are still unidentified; and an interview with the Eraserheads band members.